Corporate jurisdiction, academic heresy, and fraternal correction at the University of Paris, 1200-1400 - Moule, Gregory S. (Education and society in the Middle Ages and Renaissance., 2016)
In Corporate Jurisdiction, Academic Heresy, and Fraternal Correction at the University of Paris, 1200-1400, Gregory S. Moule explains how the theological faculty acquired independent jurisdiction over cases of academic heresy among its membership. He convincingly demonstrates that the faculty's jurisdiction and procedures were modelled on the pattern of a bishop and his cathedral canons. Gregory S. Moule's analysis of Pierre D'Ailly's Apologia confirms the faculty's jurisdiction and establishes that the censures of Denis Foulechat and John of Monteson were instances of judicial rather than fraternal correction. Medieval discussions of Judas Iscariot further clarify fraternal correction's role in the process of censure. Canon law, corporate theory, scholastic theology, and biblical commentary are employed to produce a wide-ranging, original, and thought-provoking study.